The employability skills of graduates at Kuala Terengganu community college and job placement / Faridah Mohamad - Mohamad, Faridah (2010)
In the economic situation today, it is definitely essential on being employable. Equipping with extra skills and knowledge will help graduates in job placement. Awareness to this scenario, this study is conducted and discussed employability skills of graduates at Kuala Terengganu Community College (KTCC) and job placement. Delphi technique is adopted as a research methodology. This technique is designed as a group communication process which aims to achieve convergence of opinion. This study also emphasized on employability skills development and the relationship with course or programmed offered by KTCC and job placement. It is found that course or programmed offered by KTCC and job placement has a significant relationship with employability skills. This finding has concluded that academic qualification and technical knowledge is essential as well as employability skills to ensure graduates from KTCC have a good reputation in job placement in the future. KTCC and employers both have important role to play in assist the development of employability skills such as campus talk from employers and prepared specific employability modules in effort to providing job and work placement, internship and opportunities to graduates at KTCC.